Memes as Political Discourse: A Semiotic Analysis of Palestine-Israeli Conflict - Alam, Sandi Nur; Farida, Alief Noor (Journal of English Language and Education, 2025)
This study aims to explore how Instagram memes related to the Palestine-Israeli conflict convey political narratives through both denotative and connotative meanings. Using Roland Barthes’ semiotic framework, a descriptive qualitative method was employed to analyse 60 memes tagged with #Palestinememes and #Israelmemes. The analysis focused on the interaction between visual and textual elements and their role in constructing meaning. The findings reveal nine dominant themes, including state delegitimisation, opponent dehumanisation, and media propaganda. Denotation provides literal anchors, while connotation embeds ideological stances, such as the keffiyeh symbolising Palestinian identity or the Star of David representing Israeli statehood. The results indicate that memes serve as condensed political texts, allowing users to share emotionally impactful messages that shape public perceptions. The study highlights the role of memes in digital agenda-setting and emphasises the necessity of critical media literacy when engaging with political content on multimodal platforms.